Achieving Restraint Reduction in a State Psychiatric Hospital: A Lean Six Sigma Project - T. Kinter, Kenneth (International Journal of Psychosocial Rehabilitation, 2017)
This paper details a project initiated and performed by staff at a state psychiatric hospital to reduce the use of physical restraints on one unit using Lean Thinking and Six Sigma quality improvement facilitation principles (LSS). It was hypothesized that the use of these principles would overcome some of the institutional barriers which have reduced the effectiveness of previous change efforts to reduce physical restraint. The article discusses the implications of this project for both the hospital and the state hospital system